Complexities of waqf development in Bangladesh - Hasan, Rashedul; Siraj, Siti Alawiah (Faculty of Business and Management, Universiti Teknologi MARA, 2016)
Bangladesh is coping with the problem of poverty since its independence. Recent success stories of the country in alleviating poverty have been the outcome of the efforts of several public and private initiatives. As a Muslim majority country, Bangladesh is yet to incorporate Islamic vehicles of poverty reduction in the national development strategies. Waqf has been sidelined as a mere charity even though it has historical success in producing continuous income and thus reducing poverty levels in the Muslim countries. This paper is divided into three sections. In the first part, it provides a historical overview of Waqf in Bangladesh followed by a brief description of Waqf institutions that are responsible for managing Waqf in Bangladesh. The final section discusses contemporary issues that are affecting the efficient management of Waqf funds towards making its mark in alleviating poverty from Bangladesh. In describing various problems, issues concerning governance and information disclosure were addressed that provide significant insight for different stakeholders. Information gathered through systematic literature review process indicated that Waqf institutions in Bangladesh are lacking appropriate governance mechanisms that are resulting in information asymmetry. Future research on the governance mechanisms applied by Waqf institutions and their impact on the extent and quality of information disclosure will provide further insight for the need of reform in this voluntary sector to ensure their sustainable future and contribution towards economic development in Bangladesh.